Temporomandibular disorders and traumatic brain injury: Two sides of the same coin - Talia B. Just; Steven J. Schwulst (Elsevier, 2021)
This review addresses the overlap of temporomandibular disorders (TMD) and traumatic brain injury (TBI). We explore the convergence of these two disorders as well as possible mechanisms for both conditions. We aim to demonstrate that there are similar processes underlying these conditions, and that further research into these processes is a critical unmet need. Without further exploration, clinicians may focus treatment on one disorder even though both may be contributing to the clinical presentation. We aim to present the best available data demonstrating that both TBI and TMD lie within the same clinical spectrum of disorders driven by the chronic activation of microglia-the resident innate immune cell of the central nervous system (CNS). Synaptic plasticity and central sensitization are at the core of both injury and disease processes, and the constitutive activation of microglia is complicit in both. We conclude with a call to advance the field with attention to both pre-clinical and clinical studies as well as better integration of clinical dentistry and medicine to treat these patients more effectively.